Hepatitis B vaccination in Nepalese infants: The present scenario - Adhikari, Sudhir; Sathian, Brijesh (Nepal Journal of Epidemiology, 2018)
Under the sustainable Development Agenda 2030, WHO is supporting the countries for achieving the global hepatitis goals by formulating evidence-based policy and data for action, promoting partnerships and mobilizing resources, raising awareness, preventing transmission, and also improving the screening, care and treatment services. There is an urgent need for a national policy for active and passive hepatitis B immunization to sustain our low transmission status. Nepal J Epidemiol. 2017;7(3); 694-696